2024
DOI: 10.31223/x51102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magmatic Controls on Volcanic Sulfur Emissions at the Iceland Hotspot

Eemu Ranta,
Sæmundur Halldórsson,
Bergrún Óladóttir
et al.

Abstract: Outgassing of S (as SO2) is one of the principal hazards posed by volcanic eruptions. However, S emission potentials of most volcanoes globally are poorly constrained due to a short observational record and an incomplete understanding of the magmatic processes that influence pre-eruptive S concentrations. Here, we use a compilation of published and new data from melt inclusions—which preserve magmatic S concentrations prior to eruptive degassing—from the Iceland hotspot to evaluate the effects of mantle meltin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Sulfur release ranges between 1000-1770 ppm across the RP, a typical range for Icelandic ri� basalts (Ranta et al 2024), with the largest ΔCs found in lavas from Svartsengi and Brennisteins�öll (Table 1).…”
Section: Sulfur Emissions Across the Rpmentioning
confidence: 99%
“…Sulfur release ranges between 1000-1770 ppm across the RP, a typical range for Icelandic ri� basalts (Ranta et al 2024), with the largest ΔCs found in lavas from Svartsengi and Brennisteins�öll (Table 1).…”
Section: Sulfur Emissions Across the Rpmentioning
confidence: 99%
“…Sulfur release ranges between 1000 and 1770 ppm across the RP, a typical range for Icelandic rift basalts (Ranta et al, 2024), with the largest ΔC S found in lavas from Svartsengi and Brennisteinsfjöll (Table 1). ΔC S values can be scaled by the mass of erupted material to estimate M S of individual eruptions, using published volumes of individual eruptive units, in the range of 0.01 km 3 to 0.72 km 3 (Table 1).…”
Section: Sulfur Emissions Across the Rpmentioning
confidence: 99%